Learning Through On-Farm Apprenticeships: Labor Identities and Sociocultural Reproduction within Alternative Agrifood Movements - Lorien E MacAuley; Kim L. Niewolny (Adult Education Research Conference, 2018)
On-farm apprenticeship is a site of sociocultural learning for beginning farmers, and also for identity politics, mediated by social movement learning processes. This critical ethnographic case study examines this activity.
Keywords: Beginning Farmer; Apprenticeship; Cultural Historical Activity Theory; New Social Movements; Social Reproduction